SISTEM INFORMASI GEOGRAFIS PEMETAAN PADA GEDUNG KANTOR KECAMATAN DAN KANTOR KELURAHAN DI WILAYAH KABUPATEN TUBAN - IRGIANTI, IRGIANTI NUR WIBIANA (Jurnal Vokasi Teknik Sipil, 2025)
The Village Office and District Office are facilities provided by the Tuban Regency Government, where the existence of the village office and district office has the function of improving public services, implementing government functions, and empowering the community in order to accelerate the realization of community welfare. Therefore, information regarding the mapping of the location and distribution patterns of the Village Office and District Office can be informed to the public using Geographic Information System (GIS) technology. It is hoped that people who do not know will be able to find the location of the Village Office and District Office more easily. In addition, the results of the mapping can later be used to determine the distribution pattern of the Village Office and District Office in Tuban Regency and it is hoped that this research can be a reference data for the Government in equalizing the location of the Village Office and District Office in Tuban Regency. This study uses the buffering method with ArcGIS 10.8 software to determine the distribution pattern of the Village Office and District Office in Tuban Regency. The results of this study are the distribution pattern of Village Offices and District Offices in Tuban Regency shows a dispersed pattern and the service coverage of Village Offices and District Offices can be categorized as high with a distance of 3 km.